Dividend Policy and Financial Distress: An Empirical Investigation of Troubled NYSE Firms - DeANGELO, HARRY; DeANGELO, LINDA (Journal of Finance, 1990)
ABSTRACT This paper studies the dividend policy adjustments of 80 NYSE firms to protracted financial distress as evidenced by multiple losses during 1980–1985. Almost all sample firms reduced dividends, and more than half apparently faced binding debt covenants in years they did so. Absent binding debt covenants, dividends are cut more often than omitted, suggesting that managerial reluctance is to the omission and not simply the reduction of dividends. Moreover, managers of firms with long dividend histories appear particularly reluctant to omit dividends. Finally, some dividend reductions seem strategically motivated, e.g., designed to enhance the firm's bargaining position with organized labor.